Improving MSME Digital Literacy through the Implementation of QRIS as a Cashless Payment Solution in the Digital Economy Era - Vingkan Andini; Rahmad Badri; Yauma Afriyanti; Nurul Fadilah; Siti Aisyah (Al-Qalam Institute, 2025)
This study aims to analyze the implementation of the Quick Response Code Indonesian Standard (QRIS) as a non-cash payment solution and a means of enhancing digital literacy among MSMEs. The research background is based on the low level of digital understanding among rural MSME actors, limited infrastructure, and the dominance of cash transactions, despite the belief that QRIS can improve transaction efficiency and expand market access. The study employs a qualitative approach with a case study design through in-depth interviews, observations, and documentation, supported by thematic data analysis using source and method triangulation. The findings reveal that the implementation of QRIS provides tangible benefits, including increased digital knowledge and skills among MSME actors, improved transaction efficiency, and greater business development opportunities. Young consumers demonstrate high enthusiasm for digital payments, while older age groups tend to prefer cash transactions. The main challenges include limited digital literacy, uneven internet network coverage, and cultural resistance to cashless transactions. This study concludes that QRIS not only functions as a payment instrument but also as a digital transformation medium in supporting the digital economic transformation of MSMEs.